Effect of Acute Hypoxia on Cardiorespiratory Coherence in Male Runners - Uryumtsev, Dmitriy Yu; Gultyaeva, Valentina V.; Zinchenko, Margarita I.; Baranov, Victor I.; Melnikov, Vladimir N.; Balioz, Natalia V.; Krivoschekov, Sergey G. (Frontiers in Physiology, 2020)
Understanding the mechanisms of oxygen supply regulation, which involves respiratory and cardiovascular systems, during human adaptation to intense physical activity, accompanied by hypoxemia, is important for the management of a training process. The objectives of the study were to investigate the cardiorespiratory coherence changes in the low-frequency band in response to hypoxic exposure and to verify a dependence of these changes upon sports qualification level in athletes. Twenty male runners aged 17– 25 years were exposed to acute normobaric hypoxia (10% O2) for 10 minutes. Respiration, gas exchange and heart rate were measured at baseline, during hypoxia and after the exposure. To evaluate cardiorespiratory coupling, squared coherence was calculated based on 5 sec averaged time series of heart and respiratory rhythms. Based on sports qualification level achieved over four years after the experimental testing, athletes were retrospectively divided into two groups, one with high level (HLG, n = 10) and other with middle level (MLG, n = 10). No differences in anthropometric traits were observed between the groups. In pooled group, acute hypoxia significantly increased cardiorespiratory coherence (CRC) at frequencies 0.030–0.045 Hz and 0.075 Hz. In response to hypoxia, the oxygen consumption decreased in HLG, and carbon dioxide production and ventilation increased in MLG. At 0.070-0.080 Hz frequencies in hypoxia, the CRC in HLG was higher compared to MLG. Thus, highly qualified athletes enhance intersystem integration in response to hypoxia. This finding can be a physiological sign for the prognosis of qualification level in runners.